Evaluation of Vegetable Type Cowpea Varieties for Commercial Production in the River Basin and Low Hill Areas - Pandey, YR; Pun, AB; Mishra, RC (Nepal Agriculture Research Journal, 2009)
Five vegetable type cowpea varieties were evaluated in farmer’s field with farmers participation at Chambas, Tanahu (450 masl) in two consecutive years 2003 and 2004 rainy season to identify suitable vegetable type cowpea varieties for commercial production in the river basin and low hill areas of western region. The experiment was arranged in randomized complete block design (RCBD) with 5 replications, farmer as replication. Prakash variety used as the check was earliest in flowering and days to first harvest from sowing with an average of 37 and 45 days respectively. Pod diameter and pod length among the varieties was significantly different. The biggest sized and longest pods were produced by IT 86F-2062-5 (Green) with an average of 0.990 cm in diameter and 25.60 cm in length. The highest green pod yield (4.971 t/ha) was produced by IT 86F-2062-5 (Green). Despite the earliness in flowering, fruiting and harvesting, Prakash produced the smallest (0.668 cm) and shortest (16.21 cm) pods and ultimately the lowest yield (2.443 t/ha). IT 86F-2062-5 (Green) produced the biggest size (0.990 cm diameter) and longest (24.60 cm) green pods as compared to other varieties IT 86D-792, IT 86F-2062-5 (White), IT 86D-798 and Prakash with white color, small size and fibrous pods. The results of the experiment and farmers preferences revealed that the variety IT 86F-2062-5 (Green) could be recommended for commercial production in the river basin and low hill areas of western region. Key words: Cowpea; green pods; river basin; variety; vegetable DOI: 10.3126/narj.v7i0.1861 Nepal Agriculture Research Journal Vol.7 2006 pp.16-20